The Concept of Learning Field Curriculum Development for English Subjects for Guides in Vocational High Schools - Maruanaya, Rita Fransina; Lewier, Christian Albert (Koli Journal : English Language Education, 2020)
Tourism in Indonesia continues to increase within the period 2009-2018. According to data from the Central Statistics Bureau, in 2018, the number of foreign tourists visiting Indonesia reached 15.81 million people, or grew by 2.5 times compared to 2009. Even in 2019, the government targeted foreign tourist visits to reach 18 million people. The increasing number of foreign tourists opens up great job opportunities for guides, especially tour guides with the ability to speak English and other languages ​​as support. To produce professionals in this field of work, quality education and training institutions are needed. Vocational High School (SMK) is one of the educational institutions that produces a professional workforce. However, based on data from the Central Statistics Bureau 2020, reflected from the level of education, the SMK open unemployment rate is still the highest among other education levels, which is 8.49% of 9.77 million people. This is a big question mark for SMK in Indonesia. Based on the results of previous research by the author and other sources, it is known that one of the factors affecting the lack of absorption of SMK graduates in the workforce is because their quality is still lacking. This could be due to a lack of cooperation between schools and business and industry. One solution that can answer this problem is the collaboration between SMK and DUDI in developing a curriculum for English subjects for guides. Learning Field as a concept of curriculum development for vocational education in Germany, can also be used in Indonesia in order to harmonize education in SMK with the needs of the labor market.